Penerapan Model Pembelajaran Discovery Learning Berbantuan Video Animasi untuk Meningkatkan Hasil Belajar Siswa - Irmansyah Potabuga; Ferny M. Tumbel; Femmy R. Kawuwung (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to evaluate the effectiveness of the discovery learning model assisted by animated videos in improving student learning outcomes on the material of the digestive system in humans in class VIII A SMP Negeri 1 Bolaang. This model was chosen because it can encourage students to participate more actively in learning, while also using technology to help understand more complex material. This study uses the Classroom Action Research approach which is carried out in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection to evaluate and improve the learning process. The results of the study showed that the application of the discovery learning model assisted by animated videos succeeded in improving student learning outcomes. In the first cycle, only 23.33% of students achieved complete learning, but in the second cycle, the percentage of students who completed increased to 86.66%. This increase occurs because students are starting to be more active in group discussions and more confident in expressing opinions. The use of animated videos also helps students understand the material in a more visual and fun way. This research makes an important contribution to the development of technology-based learning methods, especially in biology learning. These findings suggest that animated videos in learning can improve student engagement and their learning outcomes. This study suggests that further research be conducted to explore the application of this model to other subjects or at higher levels of education, in order to identify its broader benefits in educational contexts.